Survival in very preterm infants with congenital diaphragmatic hernia and association with prenatal imaging markers: a retrospective cohort study - Horn-Oudshoorn, Emily J. J.; Russo, Francesca M.; Deprest, Jan A.; Kipfmüller, Florian; Geipel, Annegret; Schaible, Thomas; Rafat, Neysan; Cordier, Anne-Gael; Benachi, Alexandra; Abbasi, Nimrah; Chiu, Priscilla P. L.; de Boode, Willem P.; et al. (BJOG, 2023)
Abstract Objectives To describe the outcomes of preterm born infants with congenital diaphragmatic hernia (CDH; ≤32.0?weeks of gestation) and the associations between prenatal imaging markers and survival. Design Retrospective cohort study. Setting Multicentre study in large referral centres. Population Infants with an isolated unilateral CDH, live born at 32.0?weeks or less of gestation, between January 2009 and January 2020. Methods Neonatal outcomes were evaluated for infants that were expectantly managed during pregnancy and infants that underwent fetoscopic endoluminal tracheal occlusion (FETO) therapy, separately. We evaluated the association between prenatal imaging markers and survival to discharge. Prenatal imaging markers included observed to expected lung-to-head ratio (o/e LHR), side of the defect, liver position, stomach position grade, and observed to expected total fetal lung volume (o/e TFLV). Main Outcome Measure Survival to discharge. Results We included 53 infants born at 30+4 (interquartile range 29+1?31+2) weeks. Survival in fetuses expectantly managed during pregnancy was 48% (13/27) in left-sided CDH and 33% (2/6) in right-sided CDH. Survival in fetuses that underwent FETO therapy was 50% (6/12) in left-sided CDH and 25% (2/8) in right-sided CDH. The o/e LHR at baseline was positively associated with survival in cases expectantly managed during pregnancy (odds ratio [OR] 1.20, 95% CI 1.07?1.42, p?